Salivary Oxidative Stress, Total Protein, Iron and pH in Children with β-Thalassemia Major and their Correlation with Dental Caries - Ali Amin Akbarnejad; Soleiman Mahjoub; Ahmad Tamadoni; Jila Masrour-Roudsari; Seyedali Seyedmajidi; Maryam Ghasempour (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Iron overload in β-thalassemia major leads to oxidative damage to tissues, which may have an important role in the onset and progression of oral diseases.Purpose: The aim of this study was to evaluate the salivary oxidative stress indicators, total protein, iron, and pH in children with β-thalassemia major and their relationship with the status of dental caries in comparison with healthy children.Materials and Method: In this case-control study, 68 β-thalassemia major and healthy children, who were age- and sex matched, were selected. Two mililiters of saliva was collected from each child. The pH was measured using pH meter paper. Thiobarbituric acid reactive substances (TBARS) as salivary lipid peroxidation index, total antioxidant capacity (TAC), total protein, and iron were measured by spectrophotometry. Data were analyzed by SPSS ver. 22 software with Pearson and independent samples t-test.Results: TBARS, TAC, iron and dmft index in the β-thalassemia major group were significantly higher and pH was significantly lower than the control group (p< 0.001). The total protein difference between the two groups was not significant (p= 0.081).Conclusion: Considering the higher salivary TBARS in the β-thalassemia major group, oxidative stress can be considered as a risk factor for dental caries in children with β-thalassemia major. Prescription of antioxidant supplements especially natural antioxidants in the diet of children with β-thalassemia major is recommended to reduce oxidative stress.